2013
DOI: 10.1186/1748-7161-8-9
|View full text |Cite
|
Sign up to set email alerts
|

An FE investigation simulating intra-operative corrective forces applied to correct scoliosis deformity

Abstract: BackgroundAdolescent idiopathic scoliosis (AIS) is a deformity of the spine, which may require surgical correction by attaching a rod to the patient’s spine using screws implanted in the vertebral bodies. Surgeons achieve an intra-operative reduction in the deformity by applying compressive forces across the intervertebral disc spaces while they secure the rod to the vertebra. We were interested to understand how the deformity correction is influenced by increasing magnitudes of surgical corrective forces and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 27 publications
0
42
0
1
Order By: Relevance
“…Rib cage global parameters, such as rib cage volume, spinal penetration index and rib hump angle (Dubousset et al 2003) and other morphological parameters complete the spine analysis, particularly for the deformed thorax which can raise clinically relevant issues for pulmonary restrictive disease (Sabourin et al 2010;Johnston et al 2011). Furthermore, 3D models are necessary for the development of realistic subject-specific finite element models (FEM) which are used to understand the mechanisms of initiation of structural deformation and predict treatment effects (Nie et al 2009;Clin et al 2010;Drevelle et al 2010;Little et al 2013) or used in crash simulation to investigate injury mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Rib cage global parameters, such as rib cage volume, spinal penetration index and rib hump angle (Dubousset et al 2003) and other morphological parameters complete the spine analysis, particularly for the deformed thorax which can raise clinically relevant issues for pulmonary restrictive disease (Sabourin et al 2010;Johnston et al 2011). Furthermore, 3D models are necessary for the development of realistic subject-specific finite element models (FEM) which are used to understand the mechanisms of initiation of structural deformation and predict treatment effects (Nie et al 2009;Clin et al 2010;Drevelle et al 2010;Little et al 2013) or used in crash simulation to investigate injury mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, intervertebral discs are simulated and analyzed while they considered as one-piece. 25 In some other articles, the annulus section and nucleus part are simulated and analyzed separately. 32 To investigate this issue, all the results of this section compared between one-piece and two-piece intervertebral discs.…”
Section: Resultsmentioning
confidence: 99%
“…24 After precise finite element modeling of a patient with scoliosis in the thoracic-lumbar region and estimating the number of modification forces needed, Little and his colleagues found that in addition to the internal forces, the imposition of external forces to reform this condition was essential. 25 Also, in other research, 26 according to CT-scan images, they used the finite element method to model the thoracic-lumbar region of the vertebrae of a patient with scoliosis and investigated the modified vertebrae by orthopedic rods.…”
Section: Introductionmentioning
confidence: 99%
“…They found the correlation between the intensity of the force and the angle of correction by measuring the applied force. Little et al [19] tried to find out how deformation was affected by the severity of corrective forces to predict the severity of the tension required to treat spinal curvature in scoliosis abnormalities. Their research showed that there is a direct relationship between the compressive forces of the connections used and the degree of curvature change.…”
Section: Introductionmentioning
confidence: 99%